1988
DOI: 10.1111/j.1651-2227.1988.tb10726.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast Milk Anti‐Escherichia coli Heat‐Labile Toxin IgA Antibodies Protect against Toxin‐Induced Infantile Diarrhea

Abstract: A prospective study to assess whether milk IgA antibodies against Escherichia coli heat labile-toxin protect breast-fed children against labile toxin-induced gastroenteritis was carried out among infants of a marginal urban area in Guatemala. One hundred and thirty children were kept under surveillance for diarrhea by periodic home visits. Stool specimens were collected from each child routinely every 2-3 weeks and during diarrheal episodes, to study the excretion of labile toxin-producing Escherichia coli. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(45 citation statements)
references
References 20 publications
0
44
1
Order By: Relevance
“…The protection against diarrhogenic bacteria and their toxins appears to be mediated via the milk SIgA antibodies, according to studies of infections with enterotoxigenic E. coli, Shigella, V. cholerae and G. lamblia (Glass et al 1983;Cruz et al 1988;Ruiz-Palacios et al 1990;Hayani et al 1992;Long et al 1999). The human peptide anti-secretory factor, which can be induced in human milk (Svensson et al 2004), has recently been shown to give protection against acute diarrhoea as well as prolonged diarrhoea (Zaman et al 2007).…”
Section: Breast-feeding and Diarrhoeamentioning
confidence: 99%
See 1 more Smart Citation
“…The protection against diarrhogenic bacteria and their toxins appears to be mediated via the milk SIgA antibodies, according to studies of infections with enterotoxigenic E. coli, Shigella, V. cholerae and G. lamblia (Glass et al 1983;Cruz et al 1988;Ruiz-Palacios et al 1990;Hayani et al 1992;Long et al 1999). The human peptide anti-secretory factor, which can be induced in human milk (Svensson et al 2004), has recently been shown to give protection against acute diarrhoea as well as prolonged diarrhoea (Zaman et al 2007).…”
Section: Breast-feeding and Diarrhoeamentioning
confidence: 99%
“…In clinical studies of breast-feeding it has been demonstrated that the levels of SIgA antibodies in the milk relate to protection against infections caused by enterotoxigenic E. coli, Vibrio cholerae, Campylobacter, Shigella and Giardia lamblia (Glass et al 1983;Cruz et al 1988;RuizPalacios et al 1990;Hayani et al 1992;Walterspiel et al 1994;Long et al 1999).…”
Section: Secretory Igamentioning
confidence: 99%
“…Studies evaluating colostral leukocytes have shown them to mediate ADCC in vitro (24), but inasmuch as ADCC antibody was not present in this study, their role in vivo in this situation is questionable. Five studies have identified secretory IgA in human milk as the protective agent in the prevention of illness (26)(27)(28)(29)(30). However, the possible role of anti-HSV IgA milk antibodies as detailed by WBA in protection against HSV infection is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in humans have linked protection against cholera (26), Escherichia coli toxin-mediated enteritis (27), Campylobacter diarrhea (28), and neonatal rotavirus infection (29. 30) with secretory IgA in milk.…”
mentioning
confidence: 99%
“…: +55 (61) 3307-2557; Fax: +55 (61) 3273-4608. E-mail: giuglian@unb.br virulence factors (7,8). Recently, some studies of our group demonstrated that sIgA inhibits the adherence of diffusely adherent Escherichia coli (DAEC), enteroaggregative Escherichia coli (EAEC) and Shigella flexneri to HeLa cells (1,31).…”
Section: Introductionmentioning
confidence: 99%